Compliance to anti-rabies vaccination in post-exposure prophylaxis - Ravish Haradanahalli Shankaraiah; Rachana Annadani Rajashekar; Vijayashankar Veena; Ashwath Narayana Doddabele Hanumanthaiah (Wolters Kluwer Medknow Publications, 2015)
Complete post-exposure prophylaxis is necessary to prevent rabies among all animal bite victims. It is essential for the bite victims to complete the full course of vaccination as recommended for complete protection. The present study was conducted to determine the compliance rate for anti-rabies vaccination by both intramuscular route and intradermal route and to determine the major constraints. The study was done at two municipal corporation hospitals in Bangalore, India. The compliance rate for intramuscular rabies vaccination was 60.0% and for intradermal rabies vaccination 77.0%. The major constraints were loss of wages, forgotten dates, cost incurred and distance from the hospital. Hence, the present study showed that the compliance to anti-rabies vaccination for post-exposure prophylaxis is low and is a cause of concern, as animal bite victims who do not complete the full course of vaccination are still at risk of developing rabies.